'Travail et progrès': Obligatory 'Educational' Labour in the Belgian Congo, 1933–60. (April 2018) - Fernández Soriano, Víctor
The authorities of the Belgian Congo imposed a series of compulsory workloads to the local communities under the argument that these tasks contributed to the 'education' of the native populations, which they called 'Travaux d'ordre éducatif' (TOE). Such workloads represented the main legal form of forced labour which existed in the Belgian Congo from their creation in 1933 until independence in 1960. Unlike what happened in most colonial empires, these workloads were not abolished after the Second World War. This article shows, through the case study of the province of Equateur, how these workloads were conceived and organized by the Belgian colonial administration. It seeks an answer to the question of why this form of forced labour remained legal in Congo until its independence.